(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article examines effective methods for English language learners to enhance their writing skills. It identifies key strategies such as reading critically, writing regularly, seeking a feedback, studying the craft, revising and editing, experimenting, set specific goals and also analyzing the progress. The article also highlights the importance of reading diverse texts to expand vocabulary and style. By presenting actionable insights and successful case studies, this work aims to equip educators and learners with practical tools to improve writing proficiency and foster confidence in written communication.